2023
DOI: 10.3389/fimmu.2023.1211839
|View full text |Cite
|
Sign up to set email alerts
|

IL-12/15/18-induced cell death and mitochondrial dynamics of human NK cells

Abstract: Natural killer (NK) cells are lymphocytes with potent antitumor functions and, consequently, several NK cell-based strategies have been developed for cancer immunotherapy. A remarkable therapeutic approach is the adoptive transfer of NK cells stimulated with IL-12, IL-15 and IL-18. This cytokine stimulation endows NK cells with properties that resemble immunological memory and, for this reason, they are known as cytokine-induced memory-like (CIML) NK cells. Very promising results have been reported in clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In support of this, Terren et al demonstrated that CIML activation of NK cells resulted in decreased viability, likely due in part to failed mitochondrial dynamics and mitophagy. Apoptosis resulting from activation was further confirmed with accumulation of super-oxide and release of cytochrome c in NK cells (59). T cells, particularly CD8+ T cells, undergo AICD as a form of peripheral immune regulation with signaling through Fas/FasL or TNFR2, which is particularly important for the prevention of autoimmune disease (60, 61).…”
Section: Discussionmentioning
confidence: 90%
“…In support of this, Terren et al demonstrated that CIML activation of NK cells resulted in decreased viability, likely due in part to failed mitochondrial dynamics and mitophagy. Apoptosis resulting from activation was further confirmed with accumulation of super-oxide and release of cytochrome c in NK cells (59). T cells, particularly CD8+ T cells, undergo AICD as a form of peripheral immune regulation with signaling through Fas/FasL or TNFR2, which is particularly important for the prevention of autoimmune disease (60, 61).…”
Section: Discussionmentioning
confidence: 90%
“…Recently, it has been shown that iCIML-NK cells have an accumulation of unfit mitochondria, characterized by an increase of mitochondrial superoxide levels. 37 …”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Terrén and colleagues reported that in vitro stimulated-adoptive NK cells had low viability compared to unstimulated cells. Although enhanced autophagy flux was detected after cytokines stimulation, NK cell survival was closely dependent on mitochondrial clearance, and low OPA1 levels and absence of mitophagy are responsible for a consequent accumulation of dysfunctional mitochondria and NK cell death [ 143 ]. This suggests a major role of both mitochondria dynamics and mitophagy in regulating NK cell effector functions and their transition into memory cells.…”
Section: Autophagy In Nk Cell Differentiationmentioning
confidence: 99%